2013
DOI: 10.1039/c2cp42542d
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of the structure and vibrational modes of acrylonitrile adsorbed on Cu(100)

Abstract: We present a theoretical study of the structure and vibrations of acrylonitrile adsorbed on a Cu(100) metal surface. Simulations have been carried out by means of the density functional theory adopting periodic boundary conditions and including van der Waals dispersion forces. The two most stable structures (which are almost degenerate in energy) correspond to the molecule adsorbed parallel to the metal surface. In both geometries, the vinyl (C=C) and the cyano (C≡N) groups are the anchorage sites to the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 70 publications
(66 reference statements)
2
24
0
1
Order By: Relevance
“…However, the experimental LUMO-map, in particular its on-top trimer segment (see Fig. 5d), strongly resembles the LUMO orbital distribution as calculated for a covalently interlinked (C 58 ) 3 chain shown in Fig. 5b.…”
Section: Mapping States In Multilayered Oligomerssupporting
confidence: 62%
“…However, the experimental LUMO-map, in particular its on-top trimer segment (see Fig. 5d), strongly resembles the LUMO orbital distribution as calculated for a covalently interlinked (C 58 ) 3 chain shown in Fig. 5b.…”
Section: Mapping States In Multilayered Oligomerssupporting
confidence: 62%
“…For C 20 and C 60 with equal bond lengths we get q IPQ (C 20 ) = 0.75470 and q IPQ (C 60 ) = 0.90317. We can now define the deviation from a sphere (in %) by D IPQ = 100 true( 1 q IPQ true) The program also determines the sphericity parameter of Diaz‐Tendero, q SP = ( a b ) 2 + ( a c ) 2 + ( b c ) 2 / a where a ≥ b ≥ c are the rotational constants. We deviate from the original definition by dividing the square‐root by the rotational constant a to obtain a dimensionless quantity.…”
Section: Methodsmentioning
confidence: 99%
“…The program also determines the sphericity parameter of Diaz-Tendero, [78] q SP ¼ ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi ða À bÞ 2 þ ða À cÞ 2 þ ðb À cÞ 2 q =a…”
Section: Volume Surface Area and Deviation From Spherical Symmetryunclassified
“…For the first the fully optimized geometry and the total energy of C − 60 have been obtained from the Hartree-Fock and density functional theory (DFT) calculations by ROHF/6-31G(d) and B3LYP/6-31G(d) levels respectively. Then within the optimized geometry the ab-initio calculations of the electronic structure and the total charge density of C − 60 have been performed at the same levels of theory, which is shown to provide reasonable results for small carbon clusters [13] and fullerenes [10,14], both charged and neutral. Although the inclusion of diffuse functions is usually important to obtain accurate absolute energies for anions, it has recently been shown that the 6-31G(d) and 6-31G+(d) basis sets give similar results for geometries, charge distributions, and relative energies of anionic C 60 and C 70 fullerenes [15,16].…”
Section: Methods Of Calculation 21 Ab-initio Calculationsmentioning
confidence: 99%